Performance intervention maps : 39 strategies for solving your organization's problems - Sanders, Ethan S. (American Society for Training & Development, 2001)
Readers are guided through a journey where they learn to link root causes to appropriate interventions, using cleverly constructed road maps. While the authors note that no accounting of performance interventions can ever be called complete, the list presented in this book provides a foundation from which a practitioner can begin investigating the most appropriate solutions for his or her clients. In addition to the books unique framework for approaching performance issues, readers will find advice and guidance for more than 20 performance improvement experts and practitioners who demonstrate how these principles have been applied successfully in the field.